Some issues of legal provision of financing for administrative and legal reform of decentralization in Ukraine - Piankovskyi, Vadym (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the analysis of the process of decentralization of public administration, redistribution of powers between the branches of power, changes in relations between citizens and the authorities. The issues of decentralization come to the fore in the conditions of the crisis period of Ukrainian statehood development, as this process is one of the basic conditions for independent and effective activity of local authorities.